COMPARATIVE ANALYSIS OF INTERNATIONAL INVESTMENT CLIMATES OF UZBEKISTAN AND KAZAKHSTAN: LEGAL LANDSCAPES, FDI FLOWS, AND ECONOMIC FUTURES (E Global Congress, 2025)
This paper provides a comparative analysis of the international investment climates in Uzbekistan and Kazakhstan, including relevant information about different factors that affect investment flows. This paper compares their international investment climates and economic relationships using data on the amount of FDI and its distribution on key sectors, and multinational involvement. Using macroeconomic data and trends over the past three decades, we evaluate their respective foreign direct investment (FDI) inflows, sectoral distribution, presence of multinational and transnational corporations, and economic relations with key partners such as countries and global organizations. The impact of several factors including legal frameworks, laws, tax incentives and financial instruments that play a vital role in terms of investment attraction in both nations have been studied as well. The paper concludes with SWOT analyses and actionable recommendations for Uzbekistan. The analysis reveals Kazakhstan's comparative advantage in attracting sustained FDI and therefore, suggests measures Uzbekistan can undertake to enhance its global competitiveness and attractiveness to foreign capital owners.